Reinterpretasi Pendidikan Moderat dalam Tafsir Al-Muntakhabat Karya KH. Achmad Asrori Al-Ishaqi dan Penerapannya dalam Sistem Pendidikan di Indonesia - Muh. Makhrus Ali Ridho; Lusia Mumtahana (Studia Quranika, 2025)
The increasingly complex challenges of radicalism and intolerance, including in Indonesia, make it necessary to explore the understandings of previous ulama' so that they can give birth to a comprehensive understanding of moderate education, including understanding in contemporary Sufi interpretations, especially through the work of KH. Achmad Asrori al-Ishaqi, who is a recognized figure in the world of Islamic scholarship. The aim of this research is to explore new understandings about religious moderation education in the context of contemporary Sufi interpretation. The urgency of this research is to prevent the spread of religious extremism ideas that are spread through educational channels. This research method includes text analysis of the Sufi Tafsir al-Muntakhabat, with a focus on the concepts of religious moderation education contained in the work. Analysis is carried out in depth to understand how these concepts are interpreted and applied in today's context. The results obtained in this research are that there are four moderate educational values in the Sufi commentary book al-Muntakhabat by KH. Achmad Asrori al-Ishaqi include: First, justice ('is), second, wasatiyah (middle), third, strengthening brotherhood between fellow humans (tolerance), fourth, respect for differences. Looking at some of these moderate educational values, when implemented in the curriculum they will be an important contribution to efforts to prevent radicalism and extremism as well as building a more harmonious society